Influence of Cu content on microstructure and mechanical properties of thixoformed Al−Si−Cu−Mg alloys - Salleh, Mohd Shukor; Omar, Mohd Zaidi (Elsevier, 2015)
The effects of Cu content on the microstructure and mechanical properties of thixoformed Al−6Si−хCu−0.3Mg (х= 3, 4, 5 and 6, mass fraction, %) alloys were studied. The samples were thixoformed at 50% liquid content and several of the samples were treated with the T6 heat treatment. The samples were then examined by optical microscopy (OM), scanning electron microscopy(SEM), energy dispersive X-ray (EDX) spectroscopy and X-ray diffraction (XRD) analysis, as well as hardness and tensile tests. The results show that the cooling slope casting and thixoforming process promote the formation of very fine and well distributed intermetallic compounds in the aluminium matrix and the mechanical properties of the alloys increase considerably compared with the permanent mould casting. The results also reveal that as the Cu content in the alloy increases, the hardness and tensile strength of the thixoformed alloys also increase. The ultimate tensile strength, yield strength and elongation to fracture of the thixoformed heat-treated Al−6Si−3Cu−0.3Mg alloy are 298 MPa, 201 MPa and 4.5%, respectively, whereas the values of the thixoformed heat-treated alloy with high Cu content (6%) are 361 MPa, 274 MPa and 1.1%, respectively. The fracture of the thixoformed Al−6Si−3Cu−0.3Mg alloy shows a dimple rupture, whereas in the alloy that contains the highest Cu content (6%), a cleavage fracture is observed.